مـــدى انتشار جرثومة المعدة بين طلاب وموظفي المعهد العالي للتقنيات الطبية صبراتة - سميرة أبوعجيلة القمودي (Surman Journal of Science and Technology, 2025)
This study investigated the prevalence of Helicobacter pylori infection and associated health awareness among students, faculty, and staff at the Higher Institute of Medical Technologies in Sabratha. The objectives were to determine prevalence rates by gender, identify the most affected age groups, and assess participants’ knowledge of infection, symptoms, transmission, and preventive measures. A cross-sectional survey was conducted with 100 voluntary participants representing different institutional categories. Data were obtained through a structured questionnaire addressing demographic factors (age, gender, residence, socioeconomic status), lifestyle practices linked to risk (smoking, consumption of stimulants, soft drinks, and spicy foods), and awareness regarding hygiene and prevention. Serological tests were also performed to detect H. pylori infection and immune responses. The findings demonstrated a considerable knowledge gap regarding H.pylori. Nearly half of the participants (45%) were unaware of the bacterium, 43% lacked knowledge of its clinical symptoms, and 62% were uninformed about the importance of proper hand hygiene. In addition, 56% did not recognize the risks associated with consuming unwashed fruits and vegetables. Serological results revealed a notable infection rate, with stronger IgM responses observed among females and more pronounced IgG responses in males. Overall, the results highlight both a relatively high prevalence of H. pylori infection and insufficient awareness of its transmission and prevention among the institute community. These findings emphasize the urgent need for health education programs to improve awareness and encourage preventive practices, thereby reducing the risk of infection and its long-term complications.